Breakdown characteristics and partial discharge phenomena of gas-insulated system under slightly nonuniform electric field with floating object - Chuayin, C.; Chamnong, C.; Sontayananon, N.; Kachachaveevong, T.; Nganpitak, T.; Kando, M.; Potivejkul, S.; Pattanadech, N. (My University, 2018)
The characteristics of breakdown voltage of air under slightly non uniform field with floating object was investigated experimentally. The sphere-plane electrodes with sphere diameter of 4.5 cm and plane diameter of 10 cm were used to study. The gap spacing between the sphere-plane electrodes was fixed at 3 cm. In this paper, the floating objects were divided into 2 types according to types of materials used, i.e., aluminum material represents a conductive particle and plastic material represents a nonconductive particle. The floating object position was varied between the sphere-plane electrodes in the test chamber. It was found that both types of floating objects clearly had negative effect on the breakdown voltage. Moreover, to more understand the effect of these floating objects, an ultra-high frequency sensor was used to detect partial discharge signal occurring during the experiment before breakdown occurred.
Keywords: Breakdown voltage; Floating object; Partial discharge; Sphere-plane electrode